Social policy - Bochel, Hugh M.; Daly, Guy (Routledge, 2014)
"Written by leading experts in the field, this text explores the major topics and areas in contemporary social policy, including health and social care, housing, work, education, disability, crime and criminal justice, the welfare state and examines the socio-economic, political and governmental contexts within which social policy operates. "--